Carborane‐Induced Excimer Emission of Severely Twisted Bis‐o‐Carboranyl Chrysene. (12th July 2018) - Marsh, Adam V.; Cheetham, Nathan J.; Little, Mark; Dyson, Matthew; White, Andrew J. P.; Beavis, Peter; Warriner, Colin N.; Swain, Anthony C.; Stavrinou, Paul N.; Heeney, Martin
Abstract: The synthesis of a highly twisted chrysene derivative incorporating two electron deficient o ‐carboranyl groups is reported. The molecule exhibits a complex, excitation‐dependent photoluminescence, including aggregation‐induced emission (AIE) with good quantum efficiency and an exceptionally long singlet excited state lifetime. Through a combination of detailed optical studies and theoretical calculations, the excited state species are identified, including an unusual excimer induced by the presence of o ‐carborane. This is the first time that o ‐carborane has been shown to induce excimer formation ab initio, as well as the first observation of excimer emission by a chrysene‐based small molecule in solution. Bis‐ o ‐carboranyl chrysene is thus an initial member of a new family of o ‐carboranyl phenacenes exhibiting a novel architecture for highly‐efficient multi‐luminescent fluorophores.